Adoption and trauma: Risks, recovery, and the lived experience of adoption. (August 2022) - Brodzinsky, David; Gunnar, Megan; Palacios, Jesus
Abstract: Background: Although a very heterogeneous group, adopted persons may present developmental and mental health problems of varying severity. Pre-placement adversity and trauma have often been linked to these problems. It has been also suggested that adoption itself is a psychological trauma, predisposing the individual to emotional difficulties. Objectives: This article examines the links between early adversity, trauma, and adoption. We begin by defining trauma and then describe the way in which pre-placement adversity can undermine neurobehavioral and interpersonal functioning, increasing the risk for long-term psychological difficulties. Next, we examine children's recovery when placed in a stable adoptive home. Finally, we explore adoption as a lived experience, highlighting contextual and developmental factors that facilitate the person's positive or negative attributions about being adopted, leading to varying patterns of emotional adjustment. Conclusions: Although pre-placement adversity increases adopted individuals' risk for maladjustment, the human brain and behavior are malleable, and placement in a nurturing adoptive home often facilitates recovery from early adversity, with significant heterogeneity in the extent of recovery within and across domains of functioning. While there is no evidence that early adoption is a trauma for the individual, ongoing negative life circumstances, attachment difficulties, and developmentally-mediated attributions about adoption can undermine the person's self-esteem, identity, relationships, and sense of well-being. Conclusions and suggestions for future research are offered.